Impact of legislative reform on worker fatalities in New Zealand workplaces: a 30-year retrospective population-level analysis. Issue 9 (17th March 2022) - Lilley, Rebbecca; Davie, Gabrielle; McNoe, Bronwen; Horsburgh, Simon; Driscoll, Tim R; Cryer, Colin
Abstract : Objectives: To determine the impact of major legislative changes to New Zealand's Occupational Health and Safety (OHS) legislation with the adoption of the Robens model as a means to control occupational risks on the burden and risk of work-related fatal injury (WRFI). Methods: Population-based comparison of WRFI to workers aged 15–84 years occurring during three periods: before (pre:1985–1992), after legislative reform (post-1:1993–2002) and after subsequent amendment (post-2:2003–2014). Annual age-industry standardised rates were calculated with 95% CI. Multivariable Poisson regression was used to estimate age-adjusted annual percentage changes (APC) for each period, overall and stratified by high-risk industry and occupational groups. Results: Over the 30-year period, 2053 worker deaths met the eligibility criteria. Age-adjusted APC in rates of worker WRFI changed little between periods: pre (−2.8%, 95% CI 0.0% to −5.5%); post-1 (−2.9%, 95% CI −1.3% to −4.5%) and post-2 (−2.9%, 95% CI −1.3% to −4.4%). There was no evidence of differences in slope. Variable trends in worker WRFI were observed for historically high-risk industry and occupational groups. Conclusions: The rate of worker WRFI decreased steadily over the 30-year period under examination and there was no evidence that this pattern of declining WRFI was substantially altered with the introduction of Robens-styled OHS legislative reforms. Beyond headline figures, historically high-risk groups had highly variable progress in reducing worker WRFI following legislative reform. This study demonstrates the value in including prereform data and high-risk subgroup analysis when assessing the performance of OHS legislative reforms to control occupational risks.